Lecturers' perception towards the implementation of student-centered learning approach in accounting courses / Zawati Hamzah, Tuan Zainun Tuan Mat and Fadzlina Mohd Fahmi - Hamzah, Zawati; Tuan Mat, Tuan Zainun; Mohd Fahmi, Fadzlina (Institute of Education Development (InED), 2007)
This is an exploratory study to identify lecturers' perception towards the implementation of student centered learning, the implementation strategies and any possible problems that might occur during the implementation. It was found that the lecturers are rather divided on whether 'student-centered teaching approach' is suitable for all accounting courses. The majority of the lecturers believed that this approach expose students to understand real world scenario. However, they are not quite sure whether the assessment method is enough to measure students' skills, as well as students' performance. Further, they agree that it enhances students' confidence, communication skills, independent thinking ability, self-directed learning skills and long term retention of knowledge. Lecturers think physical facilities and resources are important elements for the success of implementation. They perceived that updated knowledge is one of the possible problems that might occur.